KONTROL SOSIAL MASYARAKAT TERHADAP PERILAKU MENYIMPANG REMAJA (KASUS PACARAN DI TAMAN SYARIAH KOTA PAREPARE) - Syahrul Syam; Zakaria Zakaria; Andi Haris; Rahmat Muhammad (Department of Sociology Faculty of Social and Political Sciences, 2020)
This research explains about community social control toward deviant behavior of adolescents in Parepare City, especially community social control toward adolescents who are dating in the sharia park. Qualitative research methods were used to explore and understand the meaning of the problem studies, on the basis of case study research. There were seven informants in this research, consisting of community leaders, people who lived around the park, and visitors of the sharia park. The results of the research revealed that adolescent dating behavior was still considered in the category of relative deviation. Thus, the community that controls adolescents starting from the form, nature, and control processes are very weak. This was because the community would only control optimally when the courtship of adolescents in the sharia park had entered the stage of intimacy or sexual self-disclosure. The lack of community social control was caused by lack of socialization, government oversight and a variety of existing values and norms. Keywords: social control, deviant behavior, dating of adolescent.